LIPOXYGENASE INHIBITORY, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF SELECTED ESSENTIAL OILS - CHANDRA, HARISH; FAROOQ AH, ABAD (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate lipoxygenase inhibitory, antioxidant and antimicrobial activities of selected essential oils. Â Methods: Essential oils were obtained by hydrodistillation using a Clevenger-type apparatus and oils composition was analyzed by GC-MS. lipoxygenase inhibitory activity of essential oils were evaluated by lipoxygenase inhibition assayÂ and antioxidant activity by FRAP, DPPH and Î²-carotene-bleaching assay. Antimicrobial activity was determined by agar dilution, broth dilution and poisoned food method. Â Results: Lipoxygenase activity was inhibited significantly by C. winterinus oil and the inhibition was 96% at 12.5 Âµg/ml concentration. IC50 value of C. winterinus oil for lipoxygenase inhibitory activity was 3.98 Âµg/ml. Lipoxygenase inhibition was Â 56, 58, 60 and 51% Â by C. recutita, M. arvensis, C. martinii and C. flexuosus oil at 12.5 Âµg/ml concentration,Â respectively and Â IC 50 values were in the range of 10-12.2 Âµg/ml. Among major terpenes components of the oils lipoxygenase inhibitory activity was highest in citronellal (IC 50 value 1.66 Âµg/ml) followed by citronellol and citral. The essential oil of O. sanctum exhibited significant reducing potential and antioxidant activity. Antibacterial activity was highestÂ in C. flexuosus oil while antifungal activity was highest in C. flexuosus and in M. arvensis oil as compared to other oils. Â Â Â Conclusion:Â C. winterianus oil and its component citronellal with high antilipoxygenase activity is sutable for analgesic and anti-inflammatory purposes. C. flexuosus oil is sutable for checking of food spoilage as well as for dandruff due to high antimicrobial activity. O. sanctum oil can be used as good source of antioxidants. Â Keywords: essential oils; lipoxygenase inhibitory activity; antioxidant activity; antimicrobial activity